1982
DOI: 10.1007/bf00253576
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control and serum hormone levels in relation to retinopathy in diabetic pregnancy

Abstract: Summary. The occurrence and progression of retinopathy were related to the mean blood glucose levels and the serum concentrations of prolactin, human placental lactogen, oestradiol and progesterone in 57 pregnant insulin-dependent diabetic patients. Fifteen patients had frank retinopathy, of whom eight showed a marked increase in retinopathy. The initial blood glucose levels were significantly higher in patients whose retinopathy progressed, whereas during the second and third trimester similar blood glucose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Placental growth hormone (PGH) is known to replace pituitary growth hormone progressively in the maternal circulation from mid-gestation [109]. During pregnancy, the circulating concentrations of progesterone and PGH have been found to be increased in patients with PDR [110]. Placental growth hormone is also known to be a major regulator of maternal IGF-1 [111].…”
Section: Angiopoietic and Other Growth Factorsmentioning
confidence: 98%
“…Placental growth hormone (PGH) is known to replace pituitary growth hormone progressively in the maternal circulation from mid-gestation [109]. During pregnancy, the circulating concentrations of progesterone and PGH have been found to be increased in patients with PDR [110]. Placental growth hormone is also known to be a major regulator of maternal IGF-1 [111].…”
Section: Angiopoietic and Other Growth Factorsmentioning
confidence: 98%
“…The duration of diabetes before onset of pregnancy is the prime risk factor for the presence, severity, and progression of retinopathy during pregnancy (4). Progression of retinopathy is also associated with early onset of diabetes, high retinopathy level and suboptimal glycemic control before pregnancy, and rapid normalization of hyperglycemic blood glucose levels during pregnancy, hypertension, proteinuria, and nulliparity (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…A study by Vargas et al [31] showed that 10% of all pregnancies have complications as a result of diabetes mellitus in United States. The occurrence and progression of retinopathy were related to the mean blood glucose levels and the serum concentrations of prolactin, human placental lactogen, estradiol and progesterone in pregnant insulin-dependent diabetic patients was shown by Larinkari J et al [11]. Throughout gestation, serum prolactin concentrations were significantly lower in diabetic patients than in healthy subjects.…”
Section: Overview Of Correlation Of Sex Hormones With Diabetic Rementioning
confidence: 84%